Business Digitalization and Green Economy Practices for Enhancing the Competitiveness of Laundry MSMEs in Bekasi City - Suharyanto, Suharyanto; Magdalena, Pamela; Zahrotun Nisa, Riza; Markonah, Markonah (IMPOWERMENT SOCIETY, 2026)
The laundry MSME sector is one of the rapidly growing service sectors in urban areas, including Bekasi City. Most business owners still face challenges in using digital technology, managing financial records, and operating in an environmentally friendly manner. Therefore, this Community Service (PKM) activity was carried out through three main programs: business digitalization training (social media, websites, and digital marketing), financial record training using the Accurate Online application, and socialization of the use of environmentally friendly soap made from soap nuts. The PKM program was held on October 18, 2025, at the Taman Harapan Baru Housing Complex, Pejuang Village, Medan Satria District, Bekasi City, in collaboration with Paguyuban Manunggal Karya and Taurus Mitra Aspact Laundry. The implementation included lectures, demonstrations, hands-on practice, discussions, and technical assistance by a team of lecturers and students. The results of the activity showed an increase in MSMEs' understanding of utilizing digital platforms, the ability to generate automatic financial reports through Accurate Online, and awareness of environmentally friendly business practices. In addition, the activity also included the handover of a washing machine to support the increase in MSME production capacity. This activity has a positive impact and is becoming an empowerment model that can be replicated in other regions.